Review of Thoracic Imaging Findings Unique to Women. Issue 3 (August 2015) - Khashper, Alla; Gruber, James M.; Fraser, Richard S.; Discepola, Federico; Semionov, Alexandre
Purpose: Traditionally, indications for imaging studies of women are considered to be related to screening for and evaluation of disease of the female breast and pelvis. However, a number of chest diseases and associated intrathoracic imaging findings are unique to women and should be recognized by general radiologists, as well as chest and women-imaging specialists. Conclusions: The sex-specific findings unique to women include normal anatomical variants, primary lung disease, complications of breast and gynaecological disease, and pregnancy-related conditions. Classification, description, and illustration of gender-specific chest imaging findings are the objective of this article.